Non-Linear control strategies for attitude maneuvers in a cubeSat with three reaction wheel - Espinoza Garcia, Brayan Antonio (2021)
Development of nanosatellites with CubeSat stan-dard allow students and professionals to get involved into the aerospace technology. In nanosatellites, attitude plays an im-portant role since they can be affected by various disturbances such as gravity gradient and solar radiation. These disturbances generate a torque in the system that must be corrected in order to maintain the CubeSat behavior. In this article, the kinematic and dynamic equations applied to a CubeSat with three reaction wheels are presented. In order to provide a solution to the atti-tude maneuvering problem, three robust control laws developed by Boskovic, Dando, and Chen are presented and evaluated. Furthermore, these laws are compared with a feedback control law developed by Schaub and modified to use Quaternions. The simulated system was subjected to disturbances caused by a Gravity Gradient Torque and misalignments in the reaction wheels. The effectiveness of each law is determined using the Average of Square of the Commanded Control Torque (ASCCT), the Error Euler Angle Integration (EULERINT), the settlement time, the estimated computational cost (O), and the steady-state error (ess).